Oil politics in African resource communities: Rationales for conflict and peacebuilding process in Nigeria’s Ogoniland - Deji, Kalejaiye Omoshola (2022)
Exploitation of natural resources and degradation of the environment is breeding conflict between multinational corporations and their host communities in Africa. From oil conflict to blood diamonds, the relationship between multinational corporations and several African resource communities has remained uncordial for decades. In Nigeria, there has been an enduring conflict in the oil-rich Niger Delta region between the Ogoni community and Shell Petroleum Development Company. This study examined the rationales for conflict and peacebuilding process in Ogoniland. Data for the study was collected and analysed via qualitative method. Primary and secondary data were employed. The source of primary data includes in-depth interviews, informal conversation, personnal encounter, and visits to important sites – to verify some of the claims made by the interviewees. The secondary source of information includes articles in journals, books, archival materials, media chronicles, and reports of inquiries conducted by both governmental and nongovernmental organizations. The recorded interviews were transcribed verbatim. Thematic analysis technique was employed to analyze data; for the purpose of answering the four questions derived from research gap after review of extant literatures. Question one – considered in chapter three – investigated the ways Nigerian national politics is amplifying the oil conflict in Ogoniland. The chapter identifies exploitative laws, environmental neglect, repression and revenue deprival as the means through which Nigerian national politics has impacted and amplified the conflict in Ogoni. Question two – considered in chapter four – investigated the inconveniencies making Ogoni people protest against Shell and oil production in their communities. Findings unveiled the series of oil spill-induced inconvenience Ogoni people are facing in respect of the environment; ancestral agriculture livelihood; health; and economy of the community. Question three – considered in chapter five – examined the actions taken by Shell, Nigerian government and global authority to eradicate the ruinous oil spills inciting Ogoni. The study found that Nigerian government, UNEP, and Shell have taken series of actions, but that of Nigerian government and Shell have not produced significant results that could discourage Ogoni from conflict. Question four – considered in chapter six – explored means of reconciling the hostility between Ogoni people, Shell, and Nigerian government for peace to reign in Ogoniland. Findings show that owing to long duration and complexities, Ogoni conflict is characterised by changing contours and has evolved strongly overtime. Past efforts to resolve the impasse were flawed, thus actions to engender peace were promulgated for Shell, Nigerian government, and the people of Ogoni.